The Spirit of Trade in the Muslim Society through Coffee: A Case Study in Al Qassim - Maspul, Kurniawan Arif (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2023)
This qualitative study investigates the close relationship between the coffee trade and the Muslim population in Al Qassim, specifically in Buraydah and Unaizah. It reveals the unique cultural legacy, economic value, social dynamics, trade networks, and implications for sustainable development through a comprehensive process that includes a literature study, interviews, observation, and focus groups. The findings shed light on the rich history, rituals, and practices of the coffee trade, as well as their impact on local economies, society cohesiveness, and global linkages. This study helps to preserve cultural heritage, promote economic growth, and promote sustainable practices in the coffee trade in Al Qassim.